Clinical pharmacy services for tuberculosis management: a systematic review - Iskandar, D.; Suryanegara, F. D. A.; van Boven, J. F. M.; Postma, M. J. (Frontiers in Pharmacology, 2023)
Objective: This study aims to systematically review the content and potential effects of clinical pharmacy services in tuberculosis (TB) care management.Methods: Searches were performed in PubMed, Embase, Cochrane, Scopus, and Web of Science databases following PRISMA guidelines. Study characteristics and outcomes were extracted, and clinical pharmacy services components were characterized using the Descriptive Elements of Pharmacist Intervention Characterization Tool.Results: Twenty articles were included for full-text assessment, of which ten fulfilled inclusion criteria, comprising 1,168 patients (N=39 to 258 per study). Five were prospective cohort studies, two case-control studies, two quasi-experimental studies, and one cross-sectional study.Intervention foci within the clinical pharmacy services were medication adherence (50%), medication safety (40%), education to patients/caregivers regarding needs/beliefs (30%), optimizing medication/therapy effectiveness (30%), emphasis on HRQoL (10%) and drug selections (10%). The three most frequently applied interventions were drug information/patient counseling (80%), adverse drug reaction monitoring (50%), and drug use evaluation (20%). Based on the WHO outcomes classification, treatment success ranged from 72% to 93%, with higher cure outcomes (53-86%) than treatment completion (7-19%). Other outcomes, including isoniazid metabolites, medication counts, sputum conversion, adherence/compliance, knowledge, and quality of life, were better in the intervention group than in the comparator groups and/or improved over time. Risk of bias analysis indicated that included studies were not comparable to a randomized clinical trial.improve TB outcomes, but its evidence is still inconsistent and limited due to the lack of randomized controlled studies using the WHO outcomes classification.